Factors associated with provision of instrumental social support for physical activity in a foster parent population. (May 2015) - Dominick, Gregory M.; Saunders, Ruth P.; Friedman, Daniela B.; Hussey, James R.; Watkins, Ken W.
Abstract: Purpose: To examine demographic and psychosocial factors associated with foster parent's provision of instrumental social support for physical activity among foster youth. Method: Ninety-one foster parents completed surveys to assess perceptions of foster child physical activity (activity level, enjoyment, and coordination), five psychosocial variables from Theory of Planned Behavior (positive and negative behavioral beliefs, normative beliefs, perceived behavioral control) and self-efficacy to provide instrumental social support for youth physical activity. Associations between these variables and instrumental social support were determined using multiple regression analysis. Results: More supportive normative beliefs and higher self-efficacy for providing instrumental social support, and length of time a foster child resided in the foster parent household were significantly associated with greater provision of instrumental social support. Conclusion: Among foster parents, the perceived social expectations about providing instrumental social support and self-efficacy to provide instrumental social support for physical activity appear to be important influences on foster parent provision of instrumental social support for youth physical activity. Highlights: Foster parents can be important role models by supporting foster youth physical activity. Influences on the provision of instrumental social support are not clearly understood. Self-efficacy, normative beliefs, and placement stability were associated with instrumental support for physical activity. Perceived social pressure about providing support for youth PA and placement stability are unique findings from this study.